A rotationally-driven polyethylene terephthalate microdevice with integrated reagent mixing for multiplexed PCR amplification of DNA. Issue 40 (23rd September 2016) - DuVall, Jacquelyn A.; Le Roux, Delphine; Tsuei, An-Chi; Thompson, Brandon L.; Birch, Christopher; Li, Jingyi; Nelson, Daniel A.; Mills, Daniel L.; Ewing, Margaret M.; McLaren, Robert S.; Storts, Douglas R.; Root, Brian E.; et al.
Abstract : We demonstrate the capabilities of a centrifugal polyethylene terephthalate toner (PeT) microdevice for genetic analysis of short tandem repeats (STR) via PCR amplification. Abstract : We demonstrate the capabilities of a centrifugal polyethylene terephthalate toner (PeT) microdevice for integrated on-chip reagent mobilization, mixing, and PCR amplification for genetic analysis of short tandem repeats (STR). Fluid flow, including reagent mobilization and mixing, is achieved by centrifugal force, eliminating the need for bulky instrumentation. The use of a passive valve also eliminates the need for extra hardware and simplifies the chip and the device design. A custom-built system is capable of thermocycling through a dual Peltier clamping system, as well as variable rate spinning with a DC motor. A multiplex PCR amplification of alleles associated with 18 genomic loci was successfully performed on-chip, followed by capillary electrophoretic separation, which showed efficient amplification of DNA from multiple sources. The genetic profiles generated were 100% concordant with those obtained using conventional PCR methods. The resultant system represents a novel microfluidic PCR amplification platform that uses inexpensive PCR microdevices that are simple to fabricate, yet effective for complex, multiplexed PCR.